Strategi Penggunaan Kartu UNO Edukatif Dalam Rangka Peningkatan Keefektifan Pembelajaran Kosakata Bahasa Inggris dan Bahasa Sunda Bagi Guru SDN Pengadilan 5 Kota Bogor - Widyasari; Yudi Efendi; Afriani Afriani; Vica Ananta Kusuma; Agus Riyanto (Universitas PGRI Palembang, 2023)
The community service activity aims to provide solutions to teachers at SDN Pengadilan 5 Bogor City to improve the effectiveness of learning English and Sundanese vocabulary using the strategy of educational domino cards. This is in line with the Merdeka Belajar Curriculum Policy of the Ministry of Education, Culture, Research, and Technology, especially in the field of language development, namely for language internationalization and revitalization of regional languages. The method used is by directly practicing the use of domino cards through 3 (three) ways, namely (1) playing educational domino cards directly as playing domino cards in general; (2) playing hoe cards; and (3) playing cards by stringing sentences together. The results of the mentoring show that teachers gain new knowledge insights that are useful for their daily work to practice bilingual learning strategist at SDN Pengadilan 5 Bogor City, namely to apply the strategy of using educational dominoes to increase the effectiveness of learning English and Sundanese easily, innovatively, interestingly, not boringly, and happily. Keywords: Community Services, domino card, vocabulary learning, English, Sundanese language